Evolução das campanhas de vacinação anual contra a raiva de cães e gatos em municípios como atividade extensionista - Babboni, Selene Daniela [UNESP]; Modolo, José Rafael [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In a large part of the world and also in the Brazilian municipalities, dog populations represent a public health concern. Rabies is a worldwide zoonosis caused by a virus from the Lyssavirus genus, with fatal prognostic in almost 100% of the cases. The control of rabies in companion animals through mass vaccination must culminate with the break of the epidemiological link of disease transmission and, consequently the decrease of human rabies cases. In Brazil, in 1977, systematic measures of canine anti-rabies vaccination were initiated by the Rabies Prophylaxis National Program. This paper aims to describe the evolution of 47 years of vaccination against rabies carried out in municipalities as an extensionist activity with the materials and methods based on evolution of the accumulated experience of the Public and Animal Health Planning Discipline of the Faculty of Veterinary and Animal Science, UNESP of Botucatu / SP. Resulting in a decrease of rabies cases in the municipalities and consequently the public health protection.

Em grande parte do mundo e também nos Municípios brasileiros, as populações de cães representam um problema de saúde pública. A Raiva é uma zoonose de distribuição mundial, causada por um vírus do gênero Lyssavirus, com prognóstico fatal em quase 100% dos casos. O controle da Raiva em animais de companhia por meio da vacinação em massa deve culminar com a quebra do elo epidemiológico de transmissão da doença e, consequentemente, a diminuição dos casos de Raiva humana. No Brasil, no ano de 1977, medidas sistemáticas de vacinação antirrábica canina foram iniciadas por meio do Programa Nacional de Profilaxia da Raiva. Este trabalho tem como objetivo descrever a evolução dos 47 anos de vacinação contra a Raiva realizada em Municípios como uma atividade extencionista, tendo os materiais e métodos baseados na evolução da experiência acumulada pela Disciplina de Planejamento de Saúde Animal e Saúde Pública da Faculdade de Veterinária e Zootecnia da UNESP de Botucatu/SP. Resultando na diminuição dos casos de Raiva nos Municípios e consequentemente proteção à saúde pública.
Evolution of annual vaccination campaing against dog and cat rabies in municipalities as extensionist activity
Keywords: Rabies; Dogs; Cats; Annual vaccination campaign; Handbook; Public health; Planning; Raiva; Cães; Gatos; Campanha anual de vacinação; Manual|Saúde pública; Planejamento